Proactive spectrum handoff in distributed cognitive radio networks - Hua JIANG; Li-chuan MA; Ding-yu YAN; Nan PAN (Tongxin xuebao)
Researches on the spectrum handover in distributed cognitive radio network,and the method of proactive spectrum handoff is proposed.The model is established by spectrum sensing and the information before which shows the law authorized user follows,to predict the usage of spectrum.The cognitive user can perform spectrum handoff in advance without interference on the authorized user.At the same time,the method of spectrum selection based on the task allocation algorithm of ant colony is proposed,considering more communication parameters,making cognitive user can perform spectrum handoff as required,to ensure the uninterrupted transmission.Simulation and analysis show that,the proposed scheme can perform spectrum handoff in advance,complete transmission of the traffic in a short time and have a high flexibility for distributed cognitive radio network.